(untitled) (Journal of Pharma Insights and Research, 2024)
A prospective observational study was conducted to evaluate the prophylactic management of Deep Vein Thrombosis (DVT) in 60 patients admitted to the Intensive Care Unit of a tertiary care hospital. The study population included patients with diverse clinical conditions including orthopedic surgeries, cerebrovascular accidents, respiratory conditions, and post-operative cases. The mean age of patients was 59.8 years, with a gender distribution of 48.3% males and 51.7% females. Low Molecular Weight Heparin (LMWH), primarily Clexane (enoxaparin), was the most frequently prescribed prophylactic agent (68.3%), followed by Dabigatrol (20%), and unfractionated Heparin (5%). The standard dosing pattern observed was 0.4ml for Clexane and 220mg for Dabigatrol. The duration of prophylaxis ranged from 1 to 10 days, with an average duration of 5.4 days. Total knee replacement patients consistently received prophylaxis for 6 days. No adverse effects were reported during the study period, and no cases of DVT were documented. This study showed consistent prophylaxis patterns for specific conditions, particularly in orthopedic cases